The Impact of Intensive Short-Term Dynamic Psychotherapy (ISTDP) on Psychological Capacity, Anxiety Severity, and Functional Gastrointestinal Disorders in Psychosomatic Patients with Gastrointestinal Symptoms - Rostami Ravari, Mohammad Arash; Vaziri, Shahram; Sarafraz, Mahdireza; Rafiepoor, Amin (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to investigate the impact of Intensive Short-Term Dynamic Psychotherapy (ISTDP) on psychological capacity, anxiety severity, and functional gastrointestinal disorders in psychosomatic patients with gastrointestinal symptoms. Methodology: This research is applied in nature and utilized a quasi-experimental pretest-posttest design with a control group. The statistical population consisted of patients with gastrointestinal functional disorders who sought treatment for anxiety at the Bojika Counseling Center located in District 3 of Tehran in 2020. A sample of 16 participants was selected based on previous research and through purposive voluntary sampling. The sample was randomly assigned to experimental and control groups (8 participants per group). Participants were assessed before and after the intervention using the Beck Anxiety Inventory, the Gastrointestinal Symptom Rating Scale (GSRS), and the Ego Strength Scale. The experimental group underwent 15 sessions of ISTDP, each lasting 90 minutes, while the control group did not receive any intervention. Findings: Results from the simple mixed factorial design indicated that ISTDP was effective in reducing anxiety and gastrointestinal symptoms and in enhancing ego strength in psychosomatic patients with gastrointestinal symptoms in both the short-term (posttest) and long-term (follow-up) (P < 0.05). Conclusion: Therefore, the findings empirically support the efficacy of ISTDP in improving the condition of psychosomatic patients.